Heavy clouds, no rain. Unmasking the Polish Constitutional Tribunal challenging the primacy of the EU law and the Court of Justice in case K 3/212 - Michał Ziółkowski (Krytyka Prawa)
In 2021, the Polish Constitutional Tribunal (unconstitutionally composed) dropped a judicial bomb on the primacy of the EU law, a judicial dialogue with the Court of Justice, and a mechanism for providing the rule of law conditions by the Member States. The Tribunal, for the first time in history, recognised Articles 1(1), 2, 4(3) and 19(1) TEU unconstitutional. The text critically unpacks the Tribunal’s reasoning. It provides doctrinal explanations and a broader interpretation of the judgement in the context of the Tribunal’s past case law and the existing Polish debate about the judgment. One of the main arguments is that the current Tribunal is intellec-tually dishonest and abusive regarding constitutional law. It took advantage of recycling the previous constitutional case law, which was not so enthusiastic about the primacy of the EU law. The Tribunal follows strategies of illiberals or abusive constitutional actors, who conceal their real intentions and actions behind the veil of noble values and respected aims.